(N~ISLENNOE ISSLEDOWANIE \LEKTROSTATI^ESKIH POLEJ W PERIODI^ESKIH STRUKTURAH (B/s - (NlITWINENKO(B, (NlEONID nIKOLAEWI^s; (NsALXNIKOWA(B, (NlARISA pETROWNAs ((NkIEW (B:s (NnAUKOWA DUMKA(B,s, 1986)
(NbIBLIOGR(B.: (NS(B. 152-155 (53 (NNAZW(B.)s
(Nan uKRssr(B. (NoTD(B-(NNIE RADIOASTRONOMII IN(B-(NTA RADIOFIZIKI I \LEKTRONIKIs
Keywords: (N|LEKTRI^ESTWOs